Synthesis of biocompatible chitosan decorated silver nanoparticles biocomposites for enhanced antimicrobial and anticancer property. (December 2020) - Gopinath, V.; MubarakAli, D.; Vadivelu, Jamuna; Manjunath Kamath, S.; Syed, Asad; Elgorban, Abdallah M.
Graphical abstract: Highlights: Rapid, cost-effective PB-AgNPs synthesis and Chitosan capping was achieved. UV–vis spectrum, SEM, and EDX analysis confirmed the nanoparticles synthesis. CS@PB-AgNPs showed better bacterial inhibitory effect than uncapped PB-AgNPs. CS capping demonstrated reduced cellular toxicity to RAW264.7 macrophages and toxic to A549 lung cancer cells. Abstract: Numerous studies investigated the biosynthesis of silver nanoparticles (AgNPs); however, there is a large gap for the ideal time-consuming process and their cytotoxicity. Herein, for the first time, rapid AgNPs was synthesized in a short time span, using Piper betle leaf (PBL) extract by applying microwave exposure. PB-AgNPs antibacterial activity and cell compatibility were enhanced by capping with chitosan (CS@PB-AgNPs). The synthesized nanoparticles were characterized by bioanalytical techniques. PB-AgNPs expressed significant antibacterial activity against Gram-positive and Gram-negative bacterial pathogens, while hybrid CS@PB-AgNPs presented the enhanced bactericidal activity. In addition, PB-AgNPs exhibited IC50 value of 140 μg/mL against RAW 264.7 macrophages and 100 μg/mL against lung cancer cells while, CS capping reduced its toxicity at IC50 values of 400 μg/mL and 180 μg/mL respectively were affirmed by MTT, apoptosis and DNA damage detection. Overall it was demonstrated that CS capping could be a phenomenal finding to improve the biomedical potential of AgNPs.